algebra

posted by .

Can anyone answer these?

3/12 + 3/4x

4/(x + 3) * 3x/8

4x/15 ÷ 12x/3


13/(4x) * 16/39


(3/2)x + (5/2)


9/(4xa) - 3/4

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra 2

    Simplify the polynomial [(6x-8)-2x]-[(12x-7)-(4x-5)]. I came up with two answers: 36x^2 - 72x + 35 or -12x^2 + 8x - 2 Are either one of these the correct answer?
  2. Algebra

    Can someone please check my work for me. Q: Plot the graph of the equations 2x - 3y = 5 and 4x - 6y = 21 and interpret the result. A: 6(2x ¨C 3y = 5) = 12x ¨C 18y = 30 3(4x - 6y = 21) = 12x - 18y = 63 12x ¨C 18y = 30 + 12x - 18y …
  3. algebra

    5x -3 = 11 + 12x combine like figures add 3 to both sides to remove the 3 5x= 14+ 12x Now I get confused. If I remove the 12x I have to subtract 12x from 5x which gives me an answer of -7x=14 would the correct answer thus be x= -2?
  4. algebra

    24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please
  5. math,algebra

    (3^-1X^3)^2 x 12X^5 my work: 3/2X^6 x 12X^5= 36/2=18X^11 but the answer was 4/3X^11
  6. Algebra Answer Check

    What polynomial could you subtract from 5x^3 - 12x - x^2 + 9 - 12x^5 - 6x^4 to give a difference of 19 + 8x^3 - 18x - 19x^5 - 2x^2 - 8x^4?
  7. Algebra. Please check my answers

    Evaluate a/b+c^d for a=6,b=3,c=4 and d=5 A.42*** B.18 C.82 D.360 What is the simplified form of the expression ?
  8. Algebra 2 (Math)

    Divide 3x^3 + 3x^2 + 2x – 2 by x + 3 using long division. Check my answer please. 3x^2 – 6x + 20 3x^2 + 12x – 16 3x^2 + 12x – 16, R 58 3x^2 – 6x + 20, R -62 (I think that it's this one)
  9. Algebra II

    Find the equation of the line that passes through the points (1,4) and (2,-8). Question options: y = -3x + 9 y = 6x + 5 y = -12x + 16 y = 12x - 8 < this one is wrong.. I thought I had it right so how do I find the correct answer?
  10. Algebra

    What is the vertex form of the equation? y = -x^2+12x-4 My work: -(x^2 + 12x)-4 -(x^2 + 12x + 36)-4 + 36 Y= -(x+36)^2 + 32 Is this correct?

More Similar Questions